2020
DOI: 10.1590/1984-0462/2020/38/2018304
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Upper Limb Function of Children With Neonatal Brachial Plexus Palsy

Abstract: Objective: To compare the upper limb function and quality of life between children with neonatal brachial plexus palsy and controls with unaffected brachial plexus (typical children). Methods: Twenty-four children with neonatal brachial plexus palsy and 24 typical ones were evaluated, both groups with 10±3 years of age. The upper limb function was assessed by the Modified Mallet Scale and the Active Movement Scale, whereas quality of life was analyzed by the Pediatric Outcome Data Collection Instrument and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
2
4
0
1
Order By: Relevance
“…This research supports the findings of previous studies that youth with BPBI experience poorer HRQoL associated with mental health as well as participation restrictions. 3,9,26 Further, this study extends previous research in identifying that not only is participation reduced, but that this had direct Support for transitions to adulthood Anxiety of transitioning from pediatric services "We've been followed there for 18 years… and now all of a sudden, I'm starting to panic because I feel like I'm about to be thrown into the ocean without a life jacket on, and it's a horrible, horrible feeling" Megan's mom (17 years, she/her) negative effects on the mental health of these youth. Using mixed methods, previous studies have shown that these youth have appearance-related and body image concerns and socio-emotional health risks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This research supports the findings of previous studies that youth with BPBI experience poorer HRQoL associated with mental health as well as participation restrictions. 3,9,26 Further, this study extends previous research in identifying that not only is participation reduced, but that this had direct Support for transitions to adulthood Anxiety of transitioning from pediatric services "We've been followed there for 18 years… and now all of a sudden, I'm starting to panic because I feel like I'm about to be thrown into the ocean without a life jacket on, and it's a horrible, horrible feeling" Megan's mom (17 years, she/her) negative effects on the mental health of these youth. Using mixed methods, previous studies have shown that these youth have appearance-related and body image concerns and socio-emotional health risks.…”
Section: Discussionmentioning
confidence: 99%
“… 2 At a basic level, the stress of living with physical impairments, pain, and ongoing medical care negatively affects their health-related quality of life (HRQoL). 3 , 4 Youth with BPBI report decreased participation in self-care and leisure activities such as bathing, handwriting, swimming and eventually, choice of employment and education pursuits. 5 , 6 Though youth report decreased participation in these domains, it is unknown how these difficulties affect their mental health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[106][107][108] The 2016 iPLUTO consensus data (Table 1), although representing an important step forward, focused exclusively on motor recovery, with no inclusion of sensory outcome, pain, social integration, functional participation, or overall quality of life. 109 The current focus of iPLUTO is establishing global consensus for patient-reported outcome measures in children and in adolescents with BPBI with respect to functional status, health-related quality of life, and pain. 110 As of January of 2021, consensus has been reached on the Faces Pain Scale to evaluate pain in children 111 and the Brachial Plexus Outcome Measurement to evaluate functional status in adolescents.…”
Section: Pain In Bpbimentioning
confidence: 99%
“…Ambas as condições, PCU e PBP, evoluem com dificuldade na utilização do membro superior acometido devido às alterações de força e amplitude de movimento, desenvolvendo o "não uso aprendido" [8,9]. Estes déficits interferem no uso do membro superior, bem como no desempenho bimanual, podendo resultar em limitações de atividades simples, tais como vestir e tirar as roupas, amarrar cadarços ou colocar os sapatos, escovar os dentes, abrir o pote de biscoitos, dentre outras [10][11][12].…”
Section: Introductionunclassified